HISTOLOGI JARINGAN MANTEL TIRAM (SAIBO) PADA BEBERAPA JENIS BIVALVIA SEBAGAI ALTERNATIF IMPLANTASI MUTIARA - Eddy, La; Riandini, Rezki Amalia; Moniharapon, Mechiavel (Universitas Tanjungpura, 2019)
All types of bivalves have the potential to produce pearls. Pearls can be produced naturally and cultivated. In cultured pearls, pearl sac are obtained from saibo (slices of another bivalve mantle) that which come from pallial zone. This study wants know the structures of tissues saibo of several species of bivalves as an alternative pearls implantation. This study is conducted from January to March 2017. This study used 7 types of bivalves among others; Pinctada margaritifera, Saccostrea cucullata, Asaphis violascens, Polymesoda bengalensis, Pinna muricata, Volachlamys singaporina, and Tridacna crocea. The method used by staining Hematoxylin-Eosin. Thisstudy show results that every saibo has the different characteristic, but has a common characteristic of having outer epithelium mantle, inner epithelium mantle, muscle fibers, connective tissue and longitudinal muscle, so it can be recommended in pearls implantation Keywords : Saibo, Bivalvia, Implantasi Mutiara[H1] [H1]Disusun berdasarkan abjad